2017
DOI: 10.1007/s11248-016-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the powdery mildew susceptibility gene SmMLO1 in eggplant (Solanum melongena L.)

Abstract: Eggplant (Solanum melongena L.) is one of the most important vegetables among the Solanaceae and can be a host to fungal species causing powdery mildew (PM) disease. Specific homologs of the plant Mildew Locus O (MLO) gene family are PM susceptibility factors, as their loss of function results in a recessive form of resistance known as mlo resistance. In a previous work, we isolated the eggplant MLO homolog SmMLO1. SmMLO1 is closely related to MLO susceptibility genes characterized in other plant species. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has been reported that Act was used as a reference gene in the study of cucumber, tomato, bitter gourd, wheat and rubber tree [46][47][48][49][50]. EF1α was used as a reference gene for eggplant and petunia [51,52]. Tubulin was used as a reference gene for studying the mulberry [53], and 28SrRNA was used as a reference gene for studying the oat [54].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Act was used as a reference gene in the study of cucumber, tomato, bitter gourd, wheat and rubber tree [46][47][48][49][50]. EF1α was used as a reference gene for eggplant and petunia [51,52]. Tubulin was used as a reference gene for studying the mulberry [53], and 28SrRNA was used as a reference gene for studying the oat [54].…”
Section: Discussionmentioning
confidence: 99%